2018
DOI: 10.29252/hmj.22.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of family functioning, satisfaction of basic psychological needs and depression considering the mediatory role of emotion regulation difficulty

Abstract: Introduction: Depression is considered as a disorder that students have a susceptible environment for it and is affected by many factors. Therefore, the purpose of this study was to determine the role of satisfaction of basic psychological needs and family functioning by interdisciplinary role of emotion regulation difficulty in the prediction of depression. Methods: The method used in the study is descriptive approach by structural equation modeling. The sample consisted of 452 (207 boys and 245 girls) studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
0
5
0
3
Order By: Relevance
“…A significant positive correlation was found between family functioning and the PsyCap of high school students, with family functioning predicting PsyCap. Studies have confirmed that family plays a vital role in psychological development and socialisation ( Barth, 2017 ; Shalchi and Esmaeili Shahna, 2018 ; White et al, 2018 ). This finding is consistent with Ji et al (2018) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant positive correlation was found between family functioning and the PsyCap of high school students, with family functioning predicting PsyCap. Studies have confirmed that family plays a vital role in psychological development and socialisation ( Barth, 2017 ; Shalchi and Esmaeili Shahna, 2018 ; White et al, 2018 ). This finding is consistent with Ji et al (2018) .…”
Section: Discussionmentioning
confidence: 99%
“…Families play a vital role in adolescents’ growth, significantly affecting their physical and mental health and facilitating individual socialisation ( Barth, 2017 ; Shalchi and Esmaeili Shahna, 2018 ). Bronfenbrenner’s ecological system theory of developmental psychology refers to the interaction between an individual and the environment as a behavioural system.…”
Section: Introductionmentioning
confidence: 99%
“…Çevre, bireylerin ihtiyaçlarının karşılanmasını desteklediğinde, bireyler çevre hakkında olumlu bir değerlendirmeye sahip olmaktadırlar. Bu olumlu değerlendirme ile birlikte bireyler, sorunlar karşısında kendilerini yeterli hissetmekte ve duygularını etkin bir şekilde düzenleyebilmektedirler (Shalchi ve Shahna, 2018). Erken dönem yaşantılarında temel psikolojik ihtiyaçları karşılanmış bireylerin, duygu düzenleme becerilerine sahip oldukları ifade edilmektedir (Lopes ve diğ., 2005).…”
Section: Tartişma Sonuç Ve öNeri̇lerunclassified
“…Ayseli (2019), çalışmasında özerklik, yeterlik ve ilişkili olma ihtiyaçları karşılanmış bireylerin, duygu düzenleme güçlüklerinin azaldığını ve dolaylı olarak kendilerini affetme eğilimlerinin arttığını belirlemiştir. Shalchi ve Shahna (2018) ise üniversite öğrencileri ile gerçekleştirdikleri çalışmada, temel psikolojik ihtiyaçların doyumu ile aile içi iletişim arasındaki ilişkinin belirlenmesinde duygu düzenleme güçlüğünün aracı rolünü ele almışlardır. Çalışmada, temel psikolojik ihtiyaçları giderilen bireylerin duygu düzenleme güçlüklerinin düşük olduğu, aile içi iletişime ise olumlu katkıda bulunduğu tespit edilmiştir.…”
Section: Tartişma Sonuç Ve öNeri̇lerunclassified
See 1 more Smart Citation